Eye clinic attendance at the olympic and paralympic games Rio 2016 and its correlation to the WHO indicators on eye health. Issue 11 (8th October 2020) - Fernandes, Arthur Gustavo; Bastawrous, Andrew; Ferraz, Nívea Nunes; Hennig, Benjamin; Lima, Vagner Loduca; Viana, Rodrigo Galvao; Campos, Mauro; Furtado, João Marcello
Abstract : Objectives: To evaluate athletes' frequency of attendance at the eye clinic during the Olympic and Paralympic Games Rio 2016 and to correlate it to WHO core indicators on progress in ophthalmology care in a country. Methods: Frequencies of athletes' attendance at the eye clinic were calculated for each country. Countries were classified according to the World Bank income levels in high, upper-middle, low-middle or low-income country. Data on ophthalmology care for each country were derived from the International Agency for the Prevention of Blindness atlas. Data were analysed in view of WHO indicators for each country: visual impairment prevalence considering presenting visual acuity <6/18 to ≥3/60 in the better vision eye; number of ophthalmologists per million people and the cataract surgical rate per year, per million population. Results: The athletes' overall frequency of attendance in the eye clinic was 6.47%. Frequencies of attendance for high, upper-middle, low-middle or low-income country were 1.97%, 9.66%, 16.54% and 22.43%, respectively. A positive correlation was observed between the athletes' attendance frequency of a country and its visual impairment prevalence (r=0.2290, p=0.0017). A negative correlation was observed between the athletes' attendance frequency of a country and its eye health workforce (r=−0.2152, p=0.0026). Conclusion: Countries with highest athletes' frequencies of attendance were those that face barriers to eye care provision. These results reinforce the importance of the eye clinic service during the Olympic and Paralympic Games proving access to specialised care to athletes and members of delegation.